2018
DOI: 10.1029/2018gl077138
|View full text |Cite
|
Sign up to set email alerts
|

Improved SST‐Precipitation Intraseasonal Relationships in the ECMWF Coupled Climate Reanalysis

Abstract: The European Centre for Medium‐range Weather Forecasts (ECMWF) has produced the ocean‐atmosphere coupled reanalysis for the twentieth century, CERA‐20C, following on from the similar but atmosphere‐only reanalysis ERA‐20C. Here we demonstrate the capability of CERA‐20C in producing more physically consistent ocean and atmosphere boundary conditions, by focusing on sea surface temperature (SST)‐precipitation intraseasonal relationships. CERA‐20C reproduces well the observed SST‐precipitation correlations, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…This effect becomes less distinguishable if it is superimposed with other longer‐time air–sea coupling effects, such as the seasonal cycle or El Niño/La Niña events. Coupled data assimilation, which provides dynamically consistent SST and atmospheric initial conditions (Feng et al, ), might benefit TC predictions by reducing such atmosphere–ocean imbalances in coupled forecasts, which, at the moment, are initialized separately in the ocean and atmosphere.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect becomes less distinguishable if it is superimposed with other longer‐time air–sea coupling effects, such as the seasonal cycle or El Niño/La Niña events. Coupled data assimilation, which provides dynamically consistent SST and atmospheric initial conditions (Feng et al, ), might benefit TC predictions by reducing such atmosphere–ocean imbalances in coupled forecasts, which, at the moment, are initialized separately in the ocean and atmosphere.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A passing TC induces a cold wake in the upper ocean, due to the upwelling of cooler subsurface water and increased evaporation, forced by the strong surface wind (Chen et al, ). TCs can also cool the ocean surface through increased cloud cover with reduced downward shortwave radiation, similar to other atmospheric convective events such as equatorial waves and the MJO (e.g., Feng et al, ). These negative feedbacks change the local thermodynamic structure of the TCs through reduced upward surface heat fluxes, to discourage rapid TC intensification.…”
Section: Introductionmentioning
confidence: 90%
“…The Indian summer monsoon (ISM; June through September) is one of the most complex weather phenomena, involving coupling between the atmosphere, land, and ocean. At the boundary of the ocean and atmosphere, air-sea interactions play a key role in the coupled Earth system (Wu and Kirtman, 2005;Feng et al, 2018). The relations between sea surface temperature (SST) and precipitation are the important measures for the air-sea interactions on different temporal scales (Woolnough et al, 2000;Rajendran et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The relations between sea surface temperature (SST) and precipitation are the important measures for the air-sea interactions on different temporal scales (Woolnough et al, 2000;Rajendran et al, 2012). Recent studies (Wang et al, 2005;Rajeevan et al, 2012;Chaudhari et al, 2013Chaudhari et al, , 2016Weller et al, 2016;Feng et al, 2018) have shown that the simulation of the ISM can be improved with the exact representation of the SST-precipitation relationship. SST modulates the meteorological factors that influence the formation and evolution of different kinds of precipitating systems over tropical oceans (Gadgil et al, 1984;Schumacher and Houze, 2003;Takayabu et al, 2010;Oueslati and Bellon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen the pioneering production of Earth system reanalyses that simultaneously produce a dynamically consistent reconstruction of the atmosphere, ocean, land and seaice, although with varying complexity in the data assimilation coupling (e.g., Penny et al, 2017). These products are preliminary but provide promising results (e.g., Feng et al, 2018) and will likely be developed much further in the coming decade. Earth system reanalyses can potentially improve the representation of budgets (Mayer et al, 2017), although propagation and amplification of coupled biases and errors may occur (Zhang et al, 2013).…”
Section: A Future Outlookmentioning
confidence: 99%